Paramedic educational interventions for out-of-hospital domestic and intimate partner violence cases: A scoping review - Craig, Wesley; Hartnady, Natalie; Naidoo, Navindhra; Martin, Lorna J; Artz, Lillian (Paramedicine (Online), 2025)
Domestic and intimate partner violence are significant causes of mortality and morbidity worldwide. The act is usually serial in nature and tends to amplify in severity if not intervened. The first interaction a victim-survivor has with the healthcare system may be through a paramedic. Paramedics are opportunely placed for early violence intervention. Previous research sought to assess the impact of domestic and intimate partner violence education on healthcare professionals, primarily with in-hospital staff, however, there has been relatively minimal inquiry concerning paramedic education and practice. This study aimed to investigate evidence regarding domestic and intimate partner violence educational interventions for pre- and in-service paramedics. Additionally, we describe the nature and extent of interprofessional training and the relevant practice guidelines/policies for paramedic responses. A scoping review, utilising an a priori piloted search strategy (Medline via PubMed, Scopus, and EBSCOhost), was used to identify literature published from 2002 related to paramedic domestic and intimate partner violence interventions. Academic literature including research produced by organizations outside of conventional academic publishing were searched. A total of 1713 records were identified, and 36 were included for descriptive analysis. Major topic domains identified included teaching content and methods, professionalising best practices for public protection, intersectionality calls for interprofessional training, and the impact of educational interventions. With reports increasingly highlighting the potential role of the paramedic response to violence, there is a paucity of studies related to its improvement. Reported teaching strategies across multiple settings have some consistency. Though interventions may improve behaviour and actual/perceived knowledge and competence, there is no evidence suggesting an impact on victim-survivor experiences and outcomes. Interprofessional collaborations between out-of-hospital services, police, social workers, and in-hospital staff may be useful but remains underreported/underutilised. Future research should focus on domestic and intimate partner violence victim-survivor stakeholder engagement and intervention implementation.